Аnticipation of Postmodern Artistic Practices in Popular Culture: The Beatles - Božilović, Nikola T.; Tasić, Miloš B. (Sociološki pregled, 2019)
The paper points to the disappearance of the division of art into ’high’ and ’popular’, with a particular emphasis on popular music, which under given circumstances adopts certain aesthetic standards of classical music forms. The authors also analyse the reverse process: the popularisation of classical music, in the composing-arranging and the performing sense. Particular attention is paid to the role, status and reach of popular culture/art in contemporary postmodern ventures. In this context, the Beatles represent a paradigmatic example, due to the fact that they used a plethora of postmodern creative procedures. The authors conduct an analysis of two characteristic Beatles’ albums (Sgt. Pepper’s Lonely Hearts Club Band and The Beatles, known as ’The White Album’) that incorporate the key principles of postmodern aesthetics.